2021
DOI: 10.1111/pce.14071
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype variations of major flowering time genes in quinoa unveil their role in the adaptation to different environmental conditions

Abstract: Response to photoperiod is of major importance in crop production. It defines the adaptation of plants to local environments. Quinoa is a short-day plant which had been domesticated in the Andeans regions. We wanted to understand the adaptation to long-day conditions by studying orthologues of two major flowering time regulators of Arabidopsis, FLOWERING LOCUS T (FT) and CONSTANS (CO) in quinoa accessions with contrasting photoperiod response. By searching the quinoa reference genome sequence, we identified 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 58 publications
3
40
0
Order By: Relevance
“…Besides, we identified FLOWERING LOCUS T (CqFT2A) within pleio7.1, a QTL found in the F 2 population, exclusively. Although FT genes are described in studies related to flowering time regulation in quinoa and in C. rubrum, no flowering-time function has been specified particularly for the CqFT2A paralog (Patiranage et al 2021;Štorchová 2020). To continue towards identification of candidate genes, we mainly focused on the two pleiotropic QTL detected in F 2 and F 3 populations and identified putative candidate genes based on their known functions in flowering time and yield regulation in other species.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we identified FLOWERING LOCUS T (CqFT2A) within pleio7.1, a QTL found in the F 2 population, exclusively. Although FT genes are described in studies related to flowering time regulation in quinoa and in C. rubrum, no flowering-time function has been specified particularly for the CqFT2A paralog (Patiranage et al 2021;Štorchová 2020). To continue towards identification of candidate genes, we mainly focused on the two pleiotropic QTL detected in F 2 and F 3 populations and identified putative candidate genes based on their known functions in flowering time and yield regulation in other species.…”
Section: Discussionmentioning
confidence: 99%
“…The newest varieties show early maturity and are almost completely day-length neutral [3,9]. Moreover, Patiranage et al [10] recently identified haplotypes that induce photoperiod insensitivity associated with early flowering under long day lengths. A haplotype-based breeding strategy of pyramiding favorable alleles is suggested by the authors to breed quinoa varieties that are early maturing under long day lengths and are, thus, suitable for cultivation in northern latitudes [10].…”
Section: Introductionmentioning
confidence: 99%
“…This is correlated with the additive effects calculated for the markers with the highest LOD score within each QTL ( Table 4 ). The observed contrasting effects of PI-614889 alleles at pleio4.1 and pleio14.1 would probably complicate breeding processes, whose aim is to reduce days to flowering and plant height and increase TKW, simultaneously ( Murphy et al, 2018 ; Patiranage et al, 2021 ). In a broader sense, our results from the genome-wide epistasis analysis revealed the complexity of the regulation of days to flowering, plant height, and TKW in quinoa, which was expected given the intricated processes, such as DNA methylation, histone modification, and non-coding RNA-associated gene silencing, which underlie these traits ( Pandey et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, we identified FLOWERING LOCUS T ( CqFT2A ) within pleio7.1 , a QTL found in the F 2 population, exclusively. Although FT genes are described in studies related to flowering time regulation in quinoa and C. rubrum , no flowering-time function has been specified particularly for the CqFT2A paralog ( Štorchová, 2020 ; Patiranage et al, 2021 ). To continue toward the identification of candidate genes, we mainly focused on the two pleiotropic QTL detected in F 2 and F 3 populations and identified putative candidate genes based on their known functions in flowering time and yield regulation in other species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation